Meniere Disease-diagnosis and Management - Jasif Nisar; . Majid-Ul-Islam; Manzoor Ahmad Latoo (Current Overview on Disease and Health Research Vol. 5, 2022)
Meniere disease (MD) is characterized by the classic triad of symptoms (episodic vertigo, tinnitus, and hearing loss) is likely caused by endolymphatic hydrops of the labyrinthine system of the inner ear.The course of MD is variable.Some patients experience progressive hearing loss with infrequent vestibular symptoms; some have severe and frequent vertigo with only mild auditory symptoms; and some manifest both auditory and vestibular symptoms in equal measure. Most patients tend to cycle from active symptoms to prolonged remissions. A clinical diagnosis of MD is made based upon the following criteria: Two or more spontaneous episodes of vertigo, each lasting 20 minutes to 12 hours Audiometrically documented low- to mid-frequency sensorineural hearing loss in the affected ear Fluctuating aural symptoms (reduced or distorted hearing, tinnitus, or fullness) in the affected ear Symptoms not better accounted for by another vestibular diagnosis Although audiometric testing is a required part of the diagnostic evaluation, there is no specific diagnostic test for MD. A variety of other conditions can present with symptoms similar to MD and are often considered in the differential diagnosis.The conditions include vestibular migraine, vestibular schwannoma, multiple sclerosis (MS), transient ischemic attacks (TIAs), benign paroxysmal positional vertigo, and Cogan syndrome. Dietary and lifestyle modifications for all patients – As initial therapy for all patients with MD, (Grade 2C).If other triggers are identified (eg, nicotine, stress, monosodium glutamate [MSG]), these should also be avoided. Dietary and lifestyle modifications should be continued indefinitely Vestibular rehabilitation for persistent disequilibrium – For patients with MD and persistent disequilibrium symptoms between attacks, we suggest referral for vestibular rehabilitation therapy (Grade 2C).Although vestibular rehabilitation does not reduce the frequency of vertigo attacks, the exercise activities maximize balance and central nervous system (CNS) compensation for disequilibrium symptoms.Vestibular rehabilitation has no role in the treatment of acute vertigo due to MD. Pharmacotherapy for refractory symptoms – For all patients with MD with refractory symptoms and poor quality of life despite dietary and lifestyle interventions,we suggest the use of pharmacotherapy rather than no pharmacotherapy (Grade 2C). Betahistine and diuretics are the two options for pharmacologic therapy to reduce the severity and intensity of MD attacks. We suggest treatment with betahistine rather than diuretics, when available (Grade 2C). Acute episodes of vertigo should be managed with vestibular suppressants and antiemetics if necessary. Glucocorticoid therapy (systemic or intratympanic) for persistent symptoms – Among all patients with refractory symptoms severe enough to require further treatment beyond dietary changes, lifestyle adjustment, and first-line pharmacotherapy, there is no widely accepted agreement upon which treatment is preferred. However, we suggest treatment with glucocorticoids rather than other therapies for these patients (Grade 2C). For the majority of patients with MD and refractory, disabling vertigo symptoms despite first-line treatments, we treat with a limited course of oral glucocorticoids. For patients with MD with disabling vertigo symptoms despite first-line treatments, and in whom oral glucocorticoid therapy is contraindicated, or who through shared decision-making prefer intratympanic therapy with intratympanic glucocorticoids. Additional treatment options for patients refractory to glucocorticoid therapy – For patients with refractory MD symptoms and continued poor quality of life despite treatment with glucocorticoids (systemic or intratympanic),additional treatments are offered depending on the degree of labyrinthine function (severity of vertigo attacks and the degree of disequilibrium between attacks) and the level of hearing loss to determine the most appropriate management for an individual patient. For MD patients with preserved hearing,treatment with endolymphatic sac procedures (including decompression and/or shunting) or sacculotomy is offered; if this is unsuccessful,we typically then offer treatment with intratympanic gentamycin. For patients with MD with complete hearing loss in the affected ear, we suggest treatment with IT gentamycin rather than labyrinthectomy (Grade 2C). Labyrinthectomy is generally reserved for those patients who have disabling symptoms that persist despite treatment with intratytmpanic gentamicin.